The Relationship between Short Story Reading Habits and Narrative Writing Skills of Grade X Students at Wonorejo State Senior High School - Laili, Ulya Nurul; Hasanah, Uswatun; Fikri, Mu’tasim (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Good short story reading habits are expected to have a positive influence on narrative writing skills, which is one of the essential skills in learning Indonesian. This study aims to describe: 1) short story reading habits as an independent variable; 2) narrative writing skills as a dependent variable; 3) the relationship between short story reading habits and narrative writing skills. This study uses a quantitative approach with a correlational method. This study took place in the even semester of the 2024/2025 academic year, which was implemented at SMA Negeri Wongsorejo. The population of this study was 152 tenth-grade students of SMA Negeri Wongsorejo who submitted a questionnaire on their short story reading habits and took a narrative writing skills test. The sample was determined at 111 students based on a statistical formula and randomly selected using a technique without replacement from each population group. Data on short story reading habits were collected using a questionnaire, while data on narrative writing skills were collected using a test. Each research instrument is declared valid because it is compiled using objective and systematic procedures. Data on reading habits and narrative writing skills were analyzed using descriptive statistics. Pearson's correlation coefficient was used to analyze the level of relationship between the independent and dependent variables. The results of the study: 1) short story reading habits are categorized as moderate; 2) narrative writing skills are in the moderate category; 3) there is a positive and significant relationship between the habit of reading short stories and students' narrative writing skills, as indicated by a correlation coefficient of 0.845. Therefore, the contribution of the short story reading habit variable to the narrative writing skills variable is 0.8452, or 71.40 percent.